Separate Regulations Regarding the Recovered Territories in the Law of People’s Poland - Eckhardt, Piotr (Acta Universitatis Lodziensis. Folia Iuridica, 2021)
The paper contains an analysis of those legal regulations of the People’s Poland which were specific to the Recovered Territories and an attempt to answer the question of why such regulations were created. The following sources of law are discussed: legal acts devoted entirely to the Recovered Territories; legal acts applied to the entire territory of Poland in which some provisions were devoted exclusively to regulating the situation in these areas; legal acts that formally applied to the entire territory of Poland, but in the Recovered Territories their regulations were of particular importance. The internal regulations of the Ministry of the Recovered Territories were also examined.